Comisiones Triunfadoras 1866, 1896, 1899, 1934 - Todd, Roberto H. (My University, 1935)
Comisiones Triunfadoras 1866, 1896, 1899, 1934
Keywords: Zeno Gandía, Manuel, 1855-1930; Henna, José Julio, 1848-1924; Hostos, Eugenio María de, 1839-1903; Mariano Quiñones, Francisco, 1830-1908; Muñoz Rivera, Luis, 1859-1916; Degetau y González, Federico, 1862-1914; Matienzo Cintrón, Rosendo, 1855-1913; Acosta y Calbo, José Julián de, 1825-1891; Muñoz Marín, Luis, 1898-1980; Chardón Palacios, Carlos E., 1897-1965; Menéndez Ramos, Rafael; Fernández García, Rafael